2013
DOI: 10.7705/biomedica.v33i3.770
|View full text |Cite
|
Sign up to set email alerts
|

Infección humana por Trichostrongylus spp. en residentes de zonas urbanas de la ciudad de Salvador, Bahia, Brasil

Abstract: Results: One-hundred and ten patients (1.2%) were confirmed to be infected by Trichostrongylus spp. The positive cases were significantly more frequent in females (1.6%; p<0.05), with higher distribution in the age group between 11-20 years (1.9%), compared to those aged 51-60 (0.8%) and older than 60 years (0.9%)(p<0.05), independent of gender. Trichostrongylus spp. infections were more common from March to May (40 cases) and showed a homogeneous distribution over the other periods of the year (21-25 cases). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…The presence of unidentified Trichostrogilids egg has been already reported in L. catta ( Loudon and Sauther, 2013 ) but no previous description of T. colubriformis was made in this host. Moreover, this species has zoonotic importance, since human infections have been widely reported in several countries, and are commonly linked to the ingestion of unwashed vegetables contaminated with animal feces ( Lattès et al, 2011 ; Sato et al, 2011 ; Souza et al, 2013 ; Hidalgo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of unidentified Trichostrogilids egg has been already reported in L. catta ( Loudon and Sauther, 2013 ) but no previous description of T. colubriformis was made in this host. Moreover, this species has zoonotic importance, since human infections have been widely reported in several countries, and are commonly linked to the ingestion of unwashed vegetables contaminated with animal feces ( Lattès et al, 2011 ; Sato et al, 2011 ; Souza et al, 2013 ; Hidalgo et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Variants of Trichostrongylus were reported by Pafčo et al (2019) and Mason et al (2022) in lowland gorillas, and adult Trichostrongylus worms were found in necropsied mountain gorillas in Rwanda (Hastings, 1992). Although several cases of Trichostrongylus infections have been reported in humans in north-eastern Thailand, Lao People’s Democratic Republic (PDR) and urban areas of Salvador City, Brazil (Phosuk et al, 2013; Souza et al, 2013), human Trichostrongylus infections are considered rather incidental. We found one variant of Ternidens deminutus infecting western lowland gorillas, closely similar to the one from Mona monkeys ( Cercopithecus mona ) found in Ghana (Schindler et al, 2005); this finding also corresponded to Pafčo et al (2019), who found four T. deminutus variants infecting great apes, being closely related to the same sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Trichostrongylosis in livestock has been reported from diverse geographical settings, including Southeast Asia [ 5 ], the Middle East [ 6 ], Africa [ 7 ], Europe [ 8 , 9 ] and Australian continent [ 4 ]. Similarly, human infection has been reported from Italy [ 10 ], France [ 11 ], Morocco and Egypt [ 12 , 13 ], Brazil [ 14 ], the Caribbean [ 15 ] and Australia [ 16 ]. Iran is one of the main foci of livestock and human infections and trichostrongylosis has been reported frequently [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 89%